Strategi Sosialisasi Karang Taruna Dalam Menangani Banjir di Wilayah Kelurahan Ulijami Kecamatan Pesanggrahan Jakarta Selatan: Studi Kasus pada Kelurahan Ulijami Kecamatan Pesanggrahan Jakarta Selatan - Rafi, Ade Maulana; Saputra , Aldiansyah; Dwi, Dwi Agustina Anggraini; Setiawati , Dea Setiawati; Baskara, Muhammad Meyfin Baskara; Fahrezi , Rakaditya; Abimanyu, Naufal Rahmat al amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
Flood is one of the most frequent hydro-meteorological disasters in Indonesia, significantly affecting the social, economic, and public health aspects of communities, including in RW 01, Ulujami Subdistrict, South Jakarta. This study aims to analyze the flood risk communication strategies implemented by Karang Taruna (Youth Organization), evaluate their effectiveness, and explore challenges and opportunities for innovation. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings show that Karang Taruna plays a crucial role in public education through face-to-face outreach, collaboration with neighborhood leaders and local government, and community engagement. However, the communication strategies remain conventional, lack systematic evaluation, and are not yet optimized for digital media. Youth involvement has not fully utilized creative or participatory approaches. This study highlights the need to enhance Karang Taruna's capacity through disaster training, structured social media campaigns, and adaptive community-based communication strategies. Multi-stakeholder collaboration and local policy support are key to ensuring the sustainability of flood preparedness education. The study contributes to the development of youth-based disaster communication models and strengthens the role of grassroots organizations in building resilient communities.